A correlation between accreted stellar kinematics and dark-matter halo spin in the artemis simulations. Issue 1 (9th December 2022) - Dillamore, Adam M; Belokurov, Vasily; Evans, N Wyn; Font, Andreea S
ABSTRACT: We report a correlation between the presence of a Gaia -Sausage-Enceladus (GSE) analogue and dark-matter (DM) halo spin in the artemis simulations of Milky Way-like galaxies. The haloes which contain a large population of accreted stars on highly radial orbits (like the GSE) have lower spin on average than their counterparts with more isotropic stellar velocity distributions. The median modified spin parameters λ′ differ by a factor of ∼1.7 at the present day, with a similar value when the haloes far from virial equilibrium are removed. We also show that accreted stars make up a smaller proportion of the stellar populations in haloes containing a GSE analogue, and are stripped from satellites with stellar masses typically ∼4 times smaller. Our findings suggest that the higher spin of DM haloes without a GSE-like feature is due to mergers with large satellites of stellar mass ∼10 10 M ⊙, which do not result in prominent radially anisotropic features like the GSE.